Avaliação do sistema SIGEduc-RN - Silva, Frank Bergson Antonio Fagundes (Universidade Federal Rural do Semi-Árido, 2019)
SIGEduc (Integrated Education Management System) is a system that supports School Management and enables the monitoring of school indicators and provides modern tools for students, staff and society. This article seeks to evaluate the acceptance of the public employees of the state education network of Rio Grande do Norte that handle the SIGEduc system, with a Quality evaluation using the SERVQUAL method with some modifications, keeping the criteria of the dimensions of safety, reliability, tangibility and responsiveness . The data were collected from an online questionnaire using a Google Drive tool. With the information tabulated we can understand the level of user satisfaction.
Artigo Acadêmico
Keywords: SIGEduc; SERVQUAL; Qualidade; SIGEduc; SERVQUAL; Quality; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA